PICKLED PUMPKIN IS VALUABLE FOOD PRODUCT - T. A. Sannikova; V. A. Machulkina; L. V. Pavlov (Овощи России, 2017)
One of the main directions of the food industry development is the production of functional food products. Changes in the human’s diet structure cause that none of population group does receive necessary amount of vitamins, macro and microelements in healthy routine diet. To solve this problem, food stuffs enhanced by different ingredients enable to improve the biological and food value. The pumpkin is a valuable source of such important substances as carotene and pectin. Addition of garlic and hot pepper ingredients to process of pumpkin pickling enables to enrich the products with carbohydrates, proteins, microelements, which have low or no content in the pumpkin fruit. Therefore, the study of the influence of the different quantities of garlic and hot pepper additions on chemical composition of finished product is very important. The influence of plant additions used on chemical composition of finished product had been well determined. It was shown that through increased doses of garlic and hot pepper ingredients as compared with control, the carotene and dry matter content then decreased by 1.16%-3.43% in pickled pumpkin, while the pectin content depended on added component. The highest pectin content, 0.71% was observed at addition of 10 g. garlic ingredient per 1 kg. of raw matter, that was 4.1 times higher than control. With increased addition of hot pepper ingredient the pectin accumulation was decreasing from 0.58% in control to 0.36% in variant 10g. per 1kg. of raw matter.